The football association injury and illness surveillance study: the incidence and severity of injuries in English men's senior international football - Sprouse, B.; Alty, J.; Kemp, S.; Cowie, C.; Hennis, P.; Morris, J. G.; Cooper, S. B.; Varley, I. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Injury surveillance is an integral part of elite football given medico-legal responsibilities and the need to mitigate injury occurrence in the interests of player welfare. Long-term, large-scale studies characterising specific injury diagnosis in international football are scarce, with previous studies only examining international tournaments [1,2]. The aggregation of injuries into broad categories, a lack of injury severity analysis and the inability to assess specific match and training injury patterns limit the practical use of current literature. This study aimed to compare injury patterns and specific diagnoses in matches and training, and their associated incidence and severity, in English men`s senior international football over 8 seasons.